Changing trends in China's inequality: Key issues and main findings - Terry Sicular; Shi Li; Ximing Yue; Hiroshi Sato (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This introductory chapter provides background to and summarizes key findings from the chapters in this book, all of which share in common their use of household data from the latest round of the China Household Income Project (CHIP) survey to analyze recent trends in inequality in China. We begin with an overview of relevant economic and policy developments in China and discuss data and measurement issues. We discuss our central estimates of national income inequality based on the 2007 and 2013 CHIP survey data and make comparisons to estimates from official and other sources. Drawing on the various chapters in the book, we identify six key findings. First, during the period of study income inequality in China declined, a reversal of the several decades-long trend of rising inequality; however, the measured decline not entirely robust. Adjustments for geographic differences in costs of living or for understatement of incomes at the top of the income distribution reduce or even reverse the decline. Second, the urban-rural income gap narrowed, also representing a change from past trends. Third, income gaps within, rather than among, the East/West/Center regions remained the main source of national inequality. Fourth, household wealth rose markedly and became a key factor contributing to income inequality. Fifth, growing numbers of Chinese households attained levels of income comparable to those of middle-class households in the developed world. Sixth, absolute poverty in China continued to decline and by 2013 absolute poverty was relatively low, but poverty among the remaining poor and rising relative poverty pose continuing challenges.
Keywords: D31; O15; O53; P36; 330; China; household incomes; inequality; income distribution